Pseudomonas aeruginosa Elastase Contributes to the Establishment of Chronic Lung Colonization and Modulates the Immune Response in a Murine Model - Cigana, Cristina; Castandet, Jérôme; Sprynski, Nicolas; Melessike, Medede; Beyria, Lilha; Ranucci, Serena; Alcalá-Franco, Beatriz; Rossi, Alice; Bragonzi, Alessandra; Zalacain, Magdalena; Everett, Martin (Frontiers in Microbiology, 2021)
Chronic infection by Pseudomonas aeruginosa in cystic fibrosis (CF) patients is a major contributor to progressive lung damage and is poorly treated by available antibiotic therapy. An alternative approach to the development of additional antibiotic treatments is to identify complementary therapies which target bacterial virulence factors necessary for the establishment and/or maintenance of the chronic infection. The P. aeruginosa elastase (LasB) has been suggested as an attractive anti‐virulence target due to its extracellular location, its harmful degradative effects on host tissues and the immune system, and the potential to inhibit its activity using small molecule inhibitors. However, while the relevance of LasB in acute P. aeruginosa infection has been demonstrated, it is still unclear whether this elastase might also play a role in the early phase of chronic lung colonization. By analyzing clinical P. aeruginosa clonal isolates from a CF patient, we found that the isolate RP45, collected in the early phase of persistence, produces large amounts of active LasB, while its clonal variant RP73, collected after years of colonization, does not produce it. When a mouse model of persistent pneumonia was used, deletion of the lasB gene in RP45 resulted in a significant reduction in mean bacterial numbers and incidence of chronic lung colonization at Day 7 post-challenge compared to those mice infected with wild type RP45. Furthermore, deletion of lasB in strain RP45 also resulted in an increase in immunomodulators associated with innate and adaptive immune responses in infected animals. In contrast, deletion of the lasB gene in RP73 did not affect the establishment of chronic infection. Overall, these results indicate that LasB contributes to the adaptation of P. aeruginosa to a persistent lifestyle. In addition, these findings support pharmacological inhibition of LasB as a potentially useful therapeutic intervention for P. aeruginosa-infected CF patients prior to the establishment of a chronic infection.